PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING TERHADAP HASIL BELAJAR BIOLOGI SISWA DI SMA NEGERI MUARA LAKITAN - Irwandi Irwandi; Puput Pratama Putri (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the effect of the blended learning model on the biology learning outcomes of students at SMA Negeri Muara Lakitan. This type of research is an experimental study with the sample being class XI MIA 1 as the experimental class and XI MIA 2 as the control class with the research design in the form of a randomized control group pretest posttest design with data collection techniques using tests. The data analysis technique used to test the hypothesis in this study is to use the t-test . The results showed that there was an effect of the blended learning model on the biology learning outcomes of students at SMA Negeri Muara Lakitan, Muara Lakitan District, Musi Rawas Regency, South Sumatra Province , namely the significance level obtained using SPSS 21 showed <0.05, i.e. 0.000 . Based on the results, it can be concluded that the blended learning model can have an influence on student learning outcomes at SMA Negeri Muara Lakitan, Muara Lakitan District, Musi Rawas Regency, South Sumatra Province .